Changes in biogeographic distribution patterns of southern mid-to high latitude planktonic foraminifera during the Late Cretaceous hot to cool greenhouse climate transition - Petrizzo, Maria Rose; Huber, Brian T.; Falzoni, Francesca; MacLeod, Kenneth G. (Cretaceous Research, 2020)
The biogeographic distribution of planktonic foraminifera from southern mid-to high latitudes region are discussed to identify links between species distribution patterns and the changes in Late Cretaceous climate. We present relative abundance data for planktonic foraminifera spanning from the hot greenhouse climate of the Turonian to the cooler greenhouse of the Maastrichtian based on study of Ocean Drilling Program (ODP) holes 690C (Maud Rise), 700B (Northeast Georgia Rise), 1138A (Kerguelen Plateau) and 762C (Exmouth Plateau). These drill sites were located between 47° and 65°S paleolatitude in the southern South Atlantic and southern Indian Ocean where there is a good record of changes in vertical gradients and sea surface temperatures (SSTs) and shifts are well expressed due to amplification of global climatic variations in the circum-Antarctic region. The stratigraphic distribution of planktonic foraminiferal marker species that consistently occur at all sites enables construction of a new biozonation scheme that is applicable to the southern mid-to high latitude region. Quantitative data from planktonic foraminifera are used to examine variation in assemblage composition, permitting interpretation of changes in the patterns of surface water stratification. In addition, temporal biogeographic patterns are documented from the stratigraphic record of endemic species of the Southern Ocean and of species displaying poleward or equatorward migration. Results indicate that the broadest latitudinal expansion of the Tethyan tropical climatic belt coincided with the highest paleotemperatures of the Turonian–Santonian. The onset of significant sea surface temperature cooling in the late Santonian–early Campanian led to a progressive increase in the latitudinal temperature gradient and greater biogeographic differentiation among planktonic foraminiferal assemblages. These trends resulted in the establishment of a Transitional Bioprovince with Tethyan and Austral affinities in the southern latitudes that persisted ...